Manajemen Strategi Koperasi Jasa Keuangan Mikro Syariah (KJKS) Studi Kasus di Baitul Mal Wat tamwil (BMT) Syariah Sejahtera Boyolali - Dwi Harmoyo (IAIN Salatiga, 2012)
The purposes pf the research are: (1) to analyze the external factor andinternal factor of KJKS BMT Syariah Sejahtera. (2) To analyze the strengthen,weaknesses, opportunity, and threat of KJKS BMT Syariah Sejahtera. (3)To formulate the alternative strategic management of KJKS BMT SyariahSejahtera. The research uses descriptive qualitative method approach aboutstrategy management of KJKS BMT Syariah Sejahtera with businessenvironment analysis approach that consists of external environment andinternal environtment. The external environment consists of generalenvirontment such as: politic, economic, social, and technology (PEST) andalso industrial environment. Internal environmen tcosists of oganization aspek, moneter, weaknesses, opportunity and threat (SWOT Analysis) are formulated in alternatif strategic mangement of KJKS BMT Syariah Sejahtera. The result of the research show that general environment of KJKS BMT Syariah Sejahtera shows a good enaugh prospect. Industrial environment shpws that there isi any high competition. Internal environment shows that KJKS BMT Syariah Sejahtera has three primer competitions. Based on the SWOT Analysis, shows that in SWOT – 4K quadrant, the position of KJKS BMT Syariah Sejahtera in the I quadrant in 0,09 position for strengthen-weaknesses and 2,40 for opprtunity-threat. The position shows that the alternative strategic mangement that can be done by KJKS BMT Syariah Sejahtera is the growth strategy in corporate strategy and focus strategy in business strategy. The result of the research is aspcted useful for KJKS BMT Syariah Sejahtera and others micro syariah finance, and also for the writer